Age-specific trends in incidence and survival of out-of-hospital cardiac arrest from presumed cardiac cause in Denmark 2002–2014. (July 2020) - Winther-Jensen, Matilde; Christiansen, Mia Nielsen; Hassager, Christian; Køber, Lars; Torp-Pedersen, Christian; Hansen, Steen Møller; Lippert, Freddy; Christensen, Erika Frischknecht; Kjaergaard, Jesper; Andersson, Charlotte
Abstract: Background: The general cardiovascular health has improved throughout the last few decades for middle-aged and older individuals, but the incidence of several cardiovascular diseases is reported to increase in younger people. We aimed to assess the age-specific incidence and mortality rates associated with out-of-hospital-cardiac-arrest (OHCA) between 2002 and 2014. Methods: We used the Danish Cardiac Arrest Register to identify patients with OHCA of presumed cardiac etiology. We calculated the annual incidence rates (IR) and 30-day mortality rates (MR) in 7 age groups (18–34 years, 35–44 years, 45–54 years, 55–64 years, 65–74 years, 75–84 years and ≥85 years, and ≤50 vs. >50 years). Results: Between 2002 and 2014, IR of OHCA decreased in individuals aged 65–74 and 75–84 years (158.08 to 111.2 and 237.5 to 217.09 per 100, 000 person-years) and increased in the oldest from 201.01 to 325.4 pr. 100.000 person-years. In 18–34-years incidence of OHCA increased from 1.7 to 2.6 per 100.000 person-years. When stratifying into age ≤50 vs. >50 years, the IR deviated in those >50 years (from 117.8 in 2002 to 91 in 2008 to 117.4 in 2014100, 000 person-years). The prevalence of acute myocardial infarction and heart failure prior to OHCA increased in the younger patient group in contrast to the older segment (AMI: ≤50 years: 10% to 16%, vs. >50 years: 25% to 23%, heart failure: ≤50 years 6% to 14%, vs. >50 years: 21% to 24%). Conclusion: Over the last decades, incidence rates of OHCA decreased in individuals aged 65–84, but increased in individuals older than 85. An increase was also observed in younger individuals, potentially indicating a need for better cardiovascular disease prevention in younger adults.